Mutual dependencies: centrality in translation networks - Hanna Risku; Regina Rogl; Christina Pein-Weber (JoSTrans: The Journal of Specialised Translation)
In this paper, we approach the research object — translation networks — from a qualitative network analysis perspective and examine the adequacy and usefulness of different centrality concepts such as degree, closeness and betweenness in different translation settings. For this purpose, we carried out a qualitative multi-case field study with semi-structured interviews, ethnographic participant observation and/or online content analysis. The cases include a freelancer translating directly for author clients, the translation department of a technology company and an online amateur translation network. Our study results in several observations that appear relevant to the way translation networks are conceptualised: The translation networks in our case studies all demonstrate a high level of complexity, and all the actors involved in a network are, to a certain extent, mutually dependent on each other. These networks are not straightforward, star-shaped constellations but instead show a high degree of structural polymorphy. Likewise, centrality is not completely predetermined by the actual resources available, e.g. through a large number of potential clients and subcontractors or the access to connections that comes with a role in an organisation, it also depends largely on the priorities of the individual actors. Indeed, both voluntary as well as involuntary peripheral positions were identified.